Getting the Joke: Shakespeare, Time, and Interface. (3rd July 2019) - Werier, Clifford
ABSTRACT: Phenomenological practice is used to observe how media-specific interfaces with consciousness condition the temporal experience of Shakespeare. By focusing on the phenomenology of a short but dense comedic passage, I observe the crucial importance of time and timing to comic delivery and reception across media. Three elements converge in this inquiry: (1) the temporal properties of each medium; (2) the temporal characteristics of consciousness understood phenomenologically; and (3) the embodied and linguistic features of jokes and witty exchanges. According to this model, getting the Shakespearean joke in a read play-text, live performance, or filmed/digital rendering is dependent on media-specific properties which promote differing styles of comic timing and temporally inflected interpretations. Shakespearean media and their interfaces with consciousness structure time in fundamentally different ways – and I argue that it is through such temporal movements that each medium conducts its unique phenomenological charge. Thus, the intersection of dedicated interface time constraints aligned with the reader's multiple levels of time consciousness condition each encounter with Shakespeare's time-sensitive comic structures.